The Use of Youtube Channel Vlog ‘Learning English with Bob the Canadian' to Increase Students’ Vocabulary Mastery - Umiwati, Riski; husnayaini, Ihda; Firdaus, Firdaus (LENTERNAL: Learning and Teaching Journal, 2025)
This study set out to explore whether watching the English learning vlog "Bob the Canadian" made a significant difference in students' vocabulary development compared to those who didn’t use it. The research looked at four main aspects of vocabulary: word form, pronunciation, meaning, and usage in descriptive texts. Using a quasi-experimental design, the study involved two seventh-grade classes with a total of 65 students, split into an experimental group and a control group. To track vocabulary progress, both groups took pre-tests and post-tests. The results, analyzed using paired and independent t-tests via SPSS version 26, showed a post-test score gap of 14.384 between the groups, with a standard error of 2.701. The significance level was 0.000—well below the 0.005 cutoff—indicating strong statistical evidence. Based on the findings, the alternative hypothesis was supported, while the null hypothesis was set aside. In short, the findings show that using the vlog helped improve students' vocabulary skills.